Temporal trends of mercury in eggs of five sympatrically breeding seabird species in the Canadian Arctic. (July 2016) - Braune, Birgit M.; Gaston, Anthony J.; Mallory, Mark L.
Abstract: We compared temporal trends of total mercury (Hg) in eggs of five seabird species breeding at Prince Leopold Island in the Canadian high Arctic. As changes in trophic position over time have the potential to influence contaminant temporal trends, Hg concentrations were adjusted for trophic position (measured as δ 15 N). Adjusted Hg concentrations in eggs of thick-billed murres ( Uria lomvia ) and northern fulmars ( Fulmarus glacialis ) increased from 1975 to the 1990s, followed by a plateauing of levels from the 1990s to 2014. Trends of adjusted Hg concentrations in eggs of murres, fulmars, black guillemots ( Cepphus grylle ) and black-legged kittiwakes ( Rissa tridactyla ) had negative slopes between 1993 and 2013. Adjusted Hg concentrations in glaucous gull ( Larus hyperboreus ) eggs decreased by 50% from 1993 to 2003 before starting to increase again. Glaucous gull eggs had the highest Hg concentrations followed by black guillemot eggs, and black-legged kittiwake eggs had the lowest concentrations consistently in the five years compared between 1993 and 2013. Based on published toxicological thresholds for Hg in eggs, there is little concern for adverse reproductive effects due to Hg exposure in these birds, although the levels in glaucous gull eggs warrant future scrutiny given the increase in Hg concentrations observed in recent years. There is evidence that the Hg trends observed reflect changing anthropogenic Hg emissions. It remains unclear, however, to what extent exposure to Hg on the overwintering grounds influences the Hg trends observed in the seabird eggs at Prince Leopold Island. Future research should focus on determining the extent to which Hg exposure on the breeding grounds versus the overwintering areas contribute to the trends observed in the eggs. Graphical abstract: Highlights: Mercury trends in eggs of five seabird species from the Canadian Arctic were compared. Mercury increased during the 1970s and 1980s followed by a plateauing of levels. Mercury in eggs of four species declined between 1993 and 2013. There is evidence that the Hg trends reflect changing anthropogenic Hg emissions. Glaucous gulls had the highest egg Hg levels; black-legged kittiwakes, the lowest. Abstract : Temporal trends of mercury concentrations in seabird eggs from the Canadian Arctic.